Internet como fuente de información sobre salud en pacientes de atención primaria y su influencia en la relación médico-paciente() - Marin-Torres, Viviana (Aten Primaria, 2013)
OBJECTIVE: To describe the use of the Internet by primary care patients to seek health related information, understand how they are influenced by this information, and evaluate its impact on the doctor-patient relationship. DESIGN: Cross sectional study, through self-administered survey. SETTING: One urban health center in Madrid. PARTICIPANTS: A total of 323 questionnaires were collected from patients between 14 and 75 years old who attended a physician's office for any reason, excluding illiterate patients and those with neurological or psychiatric problems preventing them from completing the survey. MEASUREMENTS: Internet usage, ability of the internet to clarify doubts regarding health issues, patient lifestyle changes, socio-demographic variables, and physician's receptivity to the use of internet by patients. RESULTS: 61% (CI 95%: 56%-67%) of patients used the Internet as a source of health information: Internet queries were able to address health doubts in 92.4% of users, 53.5% reported that the Internet changed their thinking about their health in at least one instance, 30% made behavioral changes (of which 60.1% discussed these changes with their physician), 44.3% had more questions at the physician's office, and 80.8% believe that the doctor would be willing to talk about the information found on the internet. CONCLUSIONS: Using the Internet to find information about health is very common, with positive influence on physician-patient relationship. This may be useful for achieving behavioral changes in patients and can be used as a tool in medical practice.